A New Algorithm For Co-Ordinated Heat And Power Dispatch With Wind Power System - N. Jayakumar , S. Geethanjali, S. Shanmugapriya, (International Journal of Advanced Science and Technology, 2020)
The Combined Heat and Power Dispatch (CHPD) aims to get the best electric power and thermal heat outputs in order to reduce the total operating fuel cost satisfying the power and heat demands and other operational limits. This study presents a novel approach for solving CHPD dilemma with wind power resource. An Adaptive version of Teaching Learning Based Optimization (ATLBO) algorithm tool is used in this study. Since, the Teaching Learning Based Optimization (TLBO) is a parameter-free method; the main drawback of the novel TLBO is that it gives best solution rather than a global one during its run period. Some amendment has been introduced in the learner positions in order to advance its exploration and exploitation capacity. The system running constraints such as prohibited working areas of thermal generators and feasible operating regions of cogenerators are considered. ATLBO is implemented on a standard 24 unit test system. Simulation outcome are compared with the current reports that reveal ATLBO attain the optimal solution consistently with less computational effort.